Evaluation of GeneXpert EV assay for the rapid diagnosis of enteroviral meningitis: a systematic review and meta-analysis - Min Lin; Yun-Ran Li; Qi-Wen Lan; Li-Jun Long; Jia-Qi Liu; Ying-Wen Chen; Xun-Jie Cao; Ge-Yuan Wu; Ya-Ping Li; Xu-Guang Guo (BMC, 2022)
Abstract Background GeneXpert enterovirus Assay is a PCR-based assay for Enterovirus meningitis diagnosis. However, there is currently no research about the performance of GeneXpert enterovirus assay in the diagnosis of enterovirus meningitis. Thus, a systematic review and meta-analysis is significant on the topic. Methods Embase, Cochrane Library, Web of Science, and PubMed were systematically reviewed with retrieval types. Some criteria were used to filter the studies. Only studies published in English, that made a comparison between GeneXpert enterovirus assay and RT-PCR, and could be formulated in a 2*2 table, were included. The quality of the included studies was evaluated by QUADAS-2. The effect of the GeneXpert enterovirus assay was assessed by the Sensitivity, Specificity, Positive Likelihood Ratio, Negative Likelihood Ratio, Diagnosis Odds Ratio, and summary receiver operating characteristic (SROC) curve. Publication bias and heterogeneity were evaluated by the Deeks' funnel test and Bivariate Box plot respectively. Results 7 studies were recruited in the analysis. The Pooled Sensitivity was 0.96 [95% CI (0.94-0.97)], Pooled Specificity was 0.99 [95% CI (0.98-0.99)], Positive Likelihood Ratio was 130.46 [95% CI (35.79-475.58)], Negative Likelihood Ratio was 0.04 [95% CI (0.02-0.10)], and Diagnostic Odds Ratio was 3648.23 (95% CI [963.99-13,806.72)]. In SROC Curve, Area Under Curve (AUC) was 0.9980, and Q*= 0.9849. In Deeks' funnel test, the P-value was 0.807 (P > 0.05), indicating no publication bias. The Bivariate Box plot indicated no evident heterogeneity. Conclusions The GeneXpert enterovirus assay demonstrated high diagnostic accuracy in diagnosing enterovirus meningitis.